A Single Dose of Joint in tne Treatment of Soil-ranmitted Helminthic Infections With Special Emphasis on Hookworm Infection - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1975)
Phendyne-diisothiocyanate 1.4. (JONIT) or Bitoscanate in a single, dose of 150 mg was given to 34 patients infected with hookworm. Besides habit-worm, they also harboured the common species of soil-transmitted helminths, such as Ascaris lumbricoides and Trichuris trichiura. The result of the study .shoWed-flat the drug was effective against hookworm and less effective against A. lumbricoides and T. trichiura' infections. The cure rates were 82.35%, 47.05% and 26.47 % for hookworm, A. lumbri-: coides and T. trichiura respectively. The side effects, including nausea, vomiting, diarrhoea,. giddiness or headache and abdominal discomfort were mild and transient which did not require any treatment.